Directing innovation through confrontation and democratisation: the case of platform cooperativism - Alejandro Fortuny-Sicart; Mario Pansera; Javier Lloveras (Journal of Responsible Innovation)
Technological innovation can serve a multitude of conflicting and diverse interests, often reflecting prevailing worldviews and ideologies. This article focuses on the shaping of innovation directionality in the context of digital platform capitalism, which has emerged as a powerful innovation paradigm. Simultaneously, digital platforms have sparked significant concerns regarding labour rights, economic inequalities, and injustices. We investigate the strategies of resistance, appropriation, and re-direction of digital platform technology in the case of CoopCycle, a food delivery riders’ platform cooperative. The case consists of a digital platform co-owned and governed by a federation of 70 rider cooperatives worldwide. The case study reveals that, under certain conditions, existing and well-established innovation pathways might be steered in different and more responsible directions through contestation and experimentation driven by social demands for equality, democracy and participation.